A new species of kaloula (anura: microhylidae) from north-eastern India - Das, I.; Sengupta, S.; Ahmed, M. Firoz; Dutta, S. (Centre for Herpetology, Madras Crocodile Bank Trust, 2004)
A new species of microhylid of the genus Kaloula is described from Assam and Arunachal Pradesh states, north-east India. Kaloula assamensis new species, is compared with congeners from south and south-east Asia. The new species is diagnosable in showing the following combination of characters: SVL up to 38.0 mm; tympanum not externally visible; choanae rounded, moderately large, at anterolateral edge of palate, separated by a distance greater than twice their length; postnarial ridges across palate not curving backwards towards inner edge of choanae; finger tips slightly dilated; subarticular tubercles prominent, rounded; webbing on pes to level of distal subarticular tubercles, except on toe IV, where it is to the medial tubercle, reaching tips of all toes as a narrow sheath; toe tips slightly rounded; supernumerary tubercle at base of each digit of manus; tarsus smooth, lacking folds; supratympanic fold extends from posterior edge of eye to above insertion of forelimbs; lateral glandular flank ridge absent; abdomen coarsely granular; pale brown dorsally, with a dark-edged bright yellow vertebral stripe, commencing from tip of snout and terminating near vent, where it becomes less distinct; a dark-edged broad dark brown lateral stripes, commencing from the postocular region, and extending to inguinal region; stratified colouration on posterior face of thighs and flanks; and light pericloacal ring present.